Kualitas benih dan pertumbuhan bibit cabai (Capsicum frutescens l.) pada perlakuan suhu dan wadah penyimpanan yang berbeda - Dimas Bima Taghfir; Syaiful Anwar; Budi Adi Kristanto (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Setting the temperature of the storage space of seeds and storage containers will greatly affect the quality of the seed. The aim of this research was to study the effect of temperature treatment, storage container and their interaction on seed quality and seedling growth of chilli. The study was conducted in Jetis Village and Laboratory of Plant Physiology and Breeding, Faculty of Animal and Agricultural Sciences, Diponegoro University from January to June 2017. The study was conducted using nesting experiments on the basis of Completely Randomized Design (RAL). The first factor was Storage Temperature (R1 = Room Temperature 24-29 oC, R2 = Refrigerator Temperature 5oC) and second factor was storage container nested at storage temperature that was (P1 = Alumunium foil, P2 = Paper and P3 = Plastic). Each treatment had 5 replications and each replication consisted of 100 seeds, so there were 30 experimental units. The data were analyzed by using analysis of variance (ANOVA) and continued with test of HSD (Honesty Significant Difference) 5% significance level. The results showed that the storage temperature (5oC) temperature increased the temperature and the seed vigor index was larger than the room temperature (28oC), the aluminum foil packaging produced the maximum growth potential and germination rate was higher than the plastic and paper packaging but there was no different growth rate and index vigor. Low storage space temperatures (5oC) can not maintain maximum seed quality where the 4 parameters were still below the standard quality of the seed. Seeds stored in low temperature (5oC) rooms producedfresh weight and dry weight of seedlings larger than high temperature (28oC), but the number of leaves, seed height and hypothetical vigor index were not significantly different. The aluminum foil packaging producedfresh weight and dry weight of seeds higher than plastic and paper packaging. However, the number of leaves, the height of seed and the hypothetical vigor index were notsignificantly different. Keywords : Temperature, container store, seeds quality, seedling growth, chilli.